La clasificación social del otro : formas de nombrar la “peligrosidad” en el marco del conflicto armado colombiano (2015)
ABSTRACT: This article studies the social construction of epithets that identify the actors involved in the context of the Colombian armed conflict, which are evidence of a field of symbolic, political, and ethical dispute regarding the social classification of the Other, considered to be dangerous by the institution, specifically guerrilla groups formed in the 1960s. This paper debates the changes in naming and their ideological and political weight according to different historical contexts. It analyzes three perspectives on naming: the prioritization of violence, the emphasis on the war, and the sociopolitical nature of the conflict. It suggests a less reductionist approach: that the field of social movements can aid in understanding the complexity of the phenomenon and the dynamic of contradictions at the heart of social life.